Digital-Collaboration-Based Change Management in the Implementation of the Merdeka Curriculum within the Framework of Civil Society 5.0 - Hadijah, Siti; Ramli, Akhmad (Journal of Islamic Education Students (JIES), 2025)
The national transformation toward a more adaptive and human-centered education system in the era of Civil Society 5.0 requires educational institutions, including madrasahs, to integrate digital technology into curriculum management processes. This study aims to analyze digital collaboration–based change management in the implementation of the Merdeka Curriculum at MAN Samarinda City. A qualitative case study approach was employed to identify the forms and mechanisms of digital collaboration, the supporting and inhibiting factors, and its contribution to strengthening school readiness for educational transformation. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that digital collaboration is manifested through the use of cloud-based platforms, online communication, collective development of teaching modules, and digital supervision that enhances transparency and effectiveness in curriculum management. Supporting factors include technological readiness, teachers’ digital competence, a collaborative work culture, and adaptive leadership, while inhibiting factors involve infrastructure limitations, varying levels of digital skills, and resistance to change. The study also finds that digital collaboration enhances the school’s adaptive capacity by strengthening digital competencies, expanding professional networks, and promoting knowledge-sharing practices that support the implementation of the Merdeka Curriculum. Overall, the conclusion affirm that digital collaboration is a crucial strategy for fostering an innovative and responsive educational ecosystem aligned with the demands of Civil Society 5.0.